Heterogeneity of cannabinoid ligand-induced modulations in intracellular Ca2+ signals of mouse pancreatic acinar cells in vitro - Xia Kun-kun; Shen Jian-xin; Huang Ze-bing; Song Hui-min; Gao Ming; Chen De-jie; Zhang Shui-jun; Wu Jie (Acta Pharmacologica Sinica, 2019)
We recently reported that a CB2R agonist, GW405833 (GW), reduced both the ACh-induced Ca2+ oscillations and the L-arginineinduced Ca2+ signal enhancement in mouse pancreatic acinar cells, suggesting that GW-induced inhibition may prevent the pathogenesis of acute pancreatitis. In this study, we aim to evaluate the effects of other cannabinoid ligands on Ca2+ signaling in acinar cells. Patch-clamp whole-cell recordings were applied to measure ACh-induced intracellular Ca2+ oscillations in pancreatic acinar cells acutely dissociated from wild-type (WT), CB1R knockout (KO), and CB2R KO mice, and the pharmacological effects of various cannabinoid ligands on the Ca2+ oscillations were examined. We found that all the 8 CB2R agonists tested inhibited AChinduced Ca2+ oscillations. Among them, GW, JWH133, and GP1a caused potent inhibition with IC50 values of 5.0, 6.7, and 1.2 μmol/L, respectively. In CB2R KO mice or in the presence of a CB2R antagonist (AM630), the inhibitory effects of these 3 CB2R agonists were abolished, suggesting that they acted through the CB2Rs. The CB1R agonist ACEA also induced inhibition of Ca2+ oscillations that existed in CB1R KO mice and in the presence of a CB1R antagonist (AM251), suggesting a non-CB1R effect. In WT, CB1R KO, and CB2R KO mice, a nonselective CBR agonist, WIN55,212-2, inhibited Ca2+ oscillations, which was not mediated by CB1Rs or CB2Rs. The endogenous cannabinoid substance, 2-arachidonoylglycerol (2-AG), did not show an inhibitory effect on Ca2+ oscillations. In conclusion, CB2R agonists play critical roles in modulating Ca2+ signals in mouse pancreatic acinar cells, while other cannabinoid ligands modulate Ca2+ oscillations in a heterogeneous manner through a CB receptor or non-CB-receptor mechanism.